Integrated management of root knot nematode In ginger (Zingiber officinale Rosc.) - PATNAIK, PRATIMA RAY, K C MOHANTY, S RAY, S N MOHAPATRA, P R (Journal of Spices and Aromatic Crops, 1995)
Pre-planting application ofneem cake (1 t/ha) followed by post-planting application of carbofuran (1 kg ail ha) 45 days after planting gave the best result in terms of suppression of root knot nematode population, disease intensity and increased yield of ginger (Zingiber officinale Rosc.) closely followed by application of carbofuran first followed with neem cake.